Pengujian Perfoma UUID Sebagai Primary Key Pada Database PostgreSQL Dan MongoDB - Muhamad Kamal Shamlan; Sri Winarso Martyas Edi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The selection of a primary key is crucial in database management, as it impacts database performance and scalability. This study aims to evaluate one of the trending types of primary keys among developers — UUID. The evaluation is conducted on two different databases, PostgreSQL and MongoDB, using auto-increment and MongoDB’s ObjectId as comparisons. The testing involves importing data from a CSV file and processing it in parallel to assess the efficiency of each primary key in handling data insertion. The results show that auto-increment has advantages in terms of speed and smaller storage size compared to UUID, especially in MongoDB. In PostgreSQL, the speed difference is not as significant, but auto-increment remains more efficient in storage usage. This study provides valuable insights for developers in selecting the appropriate primary key based on system performance requirements.